Pirates without borders: The propagation of cyberattacks through firms' supply chains - Matteo Crosignani; Marco Macchiavelli; André F. Silva (Federal Reserve Bank of New York, 2021)
We document the propagation effects through supply chains of the most damaging cyberattack in history and the important role of banks in mitigating its impact. Customers of directly hit firms saw reductions in revenues, profitability, and trade credit relative to similar firms. The losses were larger for customers with fewer alternative suppliers and suppliers producing high-specificity inputs. Internal liquidity buffers and increased borrowing, mainly through bank credit lines at higher rates due to increased risk, helped affected customers to maintain investment and employment. However, the shock led to persisting adjustments to the supply chain network.
Keywords: E23; G21; G3; L14; 330; cyberattacks; supply chains; credit lines